Hiding in plain sight: identifying partner stalking in intimate partner violence episodes reported to New Zealand Police - Tomkins, Jordan (Psychology, crime & law, 2025)
In relationships characterised by current or previous intimate partner violence (IPV), partner stalking is a commonly occurring phenomenon. In this study, we examined police-recorded partner stalking in IPV episode reports across 1150 cases to (a) consider the overlap between IPV and partner stalking, and the relevance of the aggressor and victim’s relationship phase to defining partner stalking; and (b) contribute empirical evidence about partner stalking prevalence rates and identification rates by police and victims. A secondary aim involved exploring possible differences between IPV cases with and without partner stalking. Although few police or victims explicitly used the label ‘stalking', we identified evidence of partner stalking within one in every seven IPV cases reported to New Zealand Police. Further, this study contributed novel analysis about relationship dynamics by adding an on–off relationship phase to the typically dichotomised categories of intact and separated relationships. In turn, we identified partner stalking relatively rarely within intact relationships; and significantly more frequently, and at similar rates, across both the separated and on–off relationship phases. Finally, we discuss implications for defining the overlap between IPV and partner stalking, police practice, and future research.